Composition and spatial distribution of subtidal decapoda on the "Reef Coast", northeastern Brazil, evaluated through a low-impact visual census technique - Bruno W. Giraldes; Petrônio A. Coelho Filho; Petrônio A. Coelho (Nauplius)
This study investigated the composition and spatial distribution of the sublittoral decapods on the reefs of Porto de Galinhas Beach, southern coast of Pernambuco, Brazil, through the Underwater Visual Census technique. Data were collected monthly, at night during full-moon tides in low tide periods from June 2004 to May 2005, using SCUBA diving and a visual census with a fixed belt transect (20 m long). Three sampling areas were defined: Confined Waters (low hydrodynamics) with shallow sites (up to 2.5 m deep); Semi-open Water (3 to 6 m deep), influenced by waves and tidal currents (moderate hydrodynamics); and Open Water (7 to 10 m deep), in the breaker zone (high hydrodynamics). A total of 6,287 individuals of 34 species belonging to the infraorders Brachyura (19 species), Achelata and Anomura (5 species each), Caridea (3 species), and Stenopodidea and Astacidea (1 species each) were collected. Two decapod assemblages were distinguished: in a habitat with low hydrodynamics and shallow (Confined) water; and in a habitat with moderate to high hydrodynamics and depths of 3 to 10 m (Semi-open and Open water). At the sites with high hydrodynamics, i.e., the Open-water Area in the breaker zone, decapod diversity was significantly lower than in the other, protected areas on the reef bench. These results suggest that the distribution of subtidal decapods on coastal reefs is influenced by depth and exposure to water stress caused by waves and currents (hydrodynamics). The visual census technique with SCUBA proved to be suitable for ecological studies on subtidal decapods.